Characterization of Lindley distribution by truncated moments. Issue 12 (18th June 2017) - Ahsanullah, M.; Ghitany, M. E.; Al-Mutairi, D. K.
ABSTRACT: In the past few years, the Lindley distribution has gained popularity for modeling lifetime data as an alternative to the exponential distribution. This paper provides two new characterizations of the Lindley distribution. The first characterization is based on a relation between left truncated moments and failure rate function. The second characterization is based on a relation between right truncated moments and reversed failure rate function.